Karakterisasi Molekuler Ikan Gurami Soang (Osphronemus goramy Lac.) berbeda uuran menggunakan Pcr-Rflp Gen Sitokrom C Oksidase 1 - Siti Nur Azizah; Agus Nuryanto; Hendro Pramono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
Gourami (Osprhronemus goramy Lac.) is a  freshwater fish that is  widely cultivated in Indonesia, particularly by fish farmer in Java. Soang strain has a faster growth rate than other strains. However, the fry that derived from a single cohort (generated from a single spawning) shows various sizes even in the same age because they have different growth rate. Differences in growth rate may occur due to differences in metabolic capabilities especially cellular respiration. Different rate of respiration can be assumed to be due to differences in the genetic component, especially on their cytochrome c oxidase 1 gene (CO1). Therefore this study aimed to determine whether there are differences in PCR-RFLP marker CO1 gene among different sizes of gourami soang strain from the same cohort so that can be used to analyze genetic diversity. This study used survey method by applying purposive random sampling. Four restriction enzymes were used  during the  research. Molecular characters were defined descriptively based on the appearance of restriction fragment on agarose gel. The result showed that soang strain which used in this study had monomorphics allele on their CO1-HindIII. PstI, BamHI, and EcoRI, could not cut the PCR products and results no RFLP markers. So that genetic variation in the used CO1 gene fragment could not be detected using HindIII, Pst1, BamH1 and EcoR1 enzymes. The three different sizes of soang strain had similar alleles or homozygous, meaning that heterozigocity value was 0 (zero). Therefore, the CO1 gene in this study could not be used as molecular character to differentiate different sizes of gourami soang strain from the same cohort.